Demand forecasting best practices - Vandeput, Nicolas (Manning Publications, 2023)
An expert demand forecaster can help an organization avoid overproduction, reduce waste, and optimize inventory levels for a real competitive advantage. Demand Forecasting Best Practices teaches you how to become that virtuoso demand forecaster. This one-of-a-kind guide reveals forecasting tools, metrics, models, and stakeholder management techniques for delivering more effective supply chains. Everything you learn has been proven and tested in a live business environment. Discover author Nicolas Vandeput's original five step framework for demand planning excellence and learn how to tailor it to your own company's needs. Illustrations and real-world examples make each concept easy to understand and easy to follow. You'll soon be delivering accurate predictions that are driving major business value. Demand Forecasting Best Practices reveals forecasting tools, metrics, models, and stakeholder management techniques for managing your demand planning process efficiently and effectively. Everything you learn has been proven and tested in a live business environment. Discover author Nicolas Vandeput's original five step framework for demand planning excellence and learn how to tailor it to your own company's needs. Illustrations and real-world examples make each concept easy to understand and easy to follow. You'll soon be delivering accurate predictions that are driving major business value.